2000
DOI: 10.1046/j.1365-2508.2000.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of an endometrial polyp in a postmenopausal patient using raloxifene

Abstract: Objective To describe the association of raloxifene use with the development of an endometrial polyp in a postmenopausal patient. Design Case report study. Results Hysterosonography and hysteroscopy showed the occurrence of an endometrial polyp in a postmenopausal patient who had been using raloxifene for 8 months. Pathological investigation showed the presence of simple hyperplasia in the polyp. Oestrogen receptors were present in both the polyp and the atrophic endometrium. Progesterone receptors, on the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The resulting elevated E 2 and P levels may contribute to myoma growth, endometrial hyperplasia, and cancer (10-13). In postmenopausal women, several studies have shown that raloxifene does not stimulate the endometrium (14-18); however, endometrial hyperplasia and endometrial polyps were reported after raloxifene use in three postmenopausal women (19,20).Few data are available regarding the gynecological effects of raloxifene in premenopausal women. In one small, shortterm study by Baker et al (21), endometrial biopsies in the follicular phase of the menstrual cycle showed a decrease in gland mitosis compared with baseline, indicating that raloxifene may not stimulate the endometrium of premenopausal women.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting elevated E 2 and P levels may contribute to myoma growth, endometrial hyperplasia, and cancer (10-13). In postmenopausal women, several studies have shown that raloxifene does not stimulate the endometrium (14-18); however, endometrial hyperplasia and endometrial polyps were reported after raloxifene use in three postmenopausal women (19,20).Few data are available regarding the gynecological effects of raloxifene in premenopausal women. In one small, shortterm study by Baker et al (21), endometrial biopsies in the follicular phase of the menstrual cycle showed a decrease in gland mitosis compared with baseline, indicating that raloxifene may not stimulate the endometrium of premenopausal women.…”
mentioning
confidence: 99%
“…The resulting elevated E 2 and P levels may contribute to myoma growth, endometrial hyperplasia, and cancer (10-13). In postmenopausal women, several studies have shown that raloxifene does not stimulate the endometrium (14-18); however, endometrial hyperplasia and endometrial polyps were reported after raloxifene use in three postmenopausal women (19,20).…”
mentioning
confidence: 99%